Algodystrophy: complex regional pain syndrome and incomplete forms - Giannotti, Stefano (Clin Cases Miner Bone Metab, 2016)
The algodystrophy, also known as complex regional pain syndrome (CRPS), is a painful disease characterized by erythema, edema, functional impairment, sensory and vasomotor disturbance. The diagnosis of CRPS is based solely on clinical signs and symptoms, and for exclusion compared to other forms of chronic pain. There is not a specific diagnostic procedure; careful clinical evaluation and additional test should lead to an accurate diagnosis. There are similar forms of chronic pain known as bone marrow edema syndrome, in which is absent the history of trauma or triggering events and the skin dystrophic changes and vasomotor alterations. These incomplete forms are self-limited, and surgical treatment is generally not needed. It is still controversial, if these forms represent a distinct self-limiting entity or an incomplete variant of CRPS. In painful unexplained conditions such as frozen shoulder, post-operative stiff shoulder or painful knee prosthesis, the algodystrophy, especially in its incomplete forms, could represent the cause.